Pembuatan Obat Kumur Alami Daun Sirih Bagi Anggota Aisyiyah di PRA Cabang Perumnas I dan Jakasampurna - Rahmi, Hanifah; Rachmania, Rizky Arcinthya; Wardani, Elly (Jurnal SOLMA, 2019)
Betel leaf is a traditional medicinal plant that is closely related to dental and oral health. Betel leaf is known as one of the natural ingredients that has the ability as a mouthwash because its activity as an antibacterial cause of dental plaque. Although it has been widely known, the use and produce of betel leaf as a mouthwash for the community needs to be socialized to maintain oral health. Community service is carried out with the aim of increasing knowledge about prevention of bad breath with natural mouthwash and simple methods of making it to the community so that they can improve their health status independently and increase economic income. The partner chosen as the location for community service is based on consideration based on the propriety of sources of data and information collected through visits and discussions. The target achieved is housewives belonging to the middle to lower economic community. The profile of the community in some residents is right to get additional knowledge and skills that are useful for improving quality of life. Community service is divided into 2 days, the first day in the form of material presentation and the second day in the form of training on making mouthwash. The results obtained were the mouthwash formula that was in accordance with the evaluation of taste, color, and odor from the orientation of the formula. The selected formula is using betel leaves and mint leaves (1:1). From this training, it is expected that members of Aisyiyah of Perumnas I Branch, as stake holders, can disseminate information on simple and affordable prices for making mouthwash to other community members.   Keywords: Mouthwash, Betel leaf, Aisyiyah, Perumnas I